The Effectiveness of the Shadow Teacher’s Role for Slow Learner Students in the Learning Process at Elementary School - Nurjanah, Siti Nurjanah; Vitri Astuti; Pina Indah Sayekti; Choiriyah Widyasari; Minsih (Mataram University, 2025)
This study aims to analyze the effectiveness of the shadow teacher’s role in the learning process of slow learners in elementary school. The research design used was a pretest-posttest control group design involving four fifth-grade slow learner students who were selected through purposive sampling at MI Muhammadiyah Karanganyar. The research instruments consisted of academic tests, questionnaires, and observations to measure changes in academic achievement and students' perceptions of learning through shadow teachers. The analysis results showed a significant difference between pretest and posttest scores (t = -5.10, df = 3, p = 0.015), indicating that special assistance was effective in improving students' learning outcomes. Furthermore, the questionnaire results revealed that students experienced positive changes in understanding, motivation, and confidence in learning. This study provides strong empirical support for implementing shadow teachers as an effective strategy in inclusive education for slow learner students in elementary schools.